Planning and control of safety in the construction refurbishment project / Ahmad Ezanee Hashim. - Hashim, Ahmad Ezanee (2004)
This study discusses a critical investigation into the needs for and interest in planning and control of safety in large refurbishment construction projects. The investigation attempted to determine from the viewpoint of large scale contractors, those critical factors which affected and influenced the safety planning and control process as well as identifying areas that affected safety of construction projects. This study also highlights the influence of the integrative mechanisms employed by refurbishment firms and their influence in safety planning performance. The integrative mechanisms include recording information, supervision and monitoring, work schedules, training and orientation and information technology systems. In addition, this study also discusses how the management organization structure of the construction firms influences the extent of the integrative mechanism used in safety planning performance. Further, it also examines the effects of employees' interest that affect and influence the safety planning and control process. A preliminary postal survey was sent to large construction firms initially, followed by semi-structured interviews with safety planning managers and supervisors of the construction firms. A final postal survey was distributed to 45-safety planning and control managers of refurbishment construction firms within the Klang valley. A total of 30 completed questionnaires were analyzed in detail and formed the database for the quantitative analysis. In addition, 14 semi-structured interviews were carried out on managers from the 30 responding construction firms. In this study both qualitative and quantitative studies were used. The result of the study indicated that there was a general lack of safety interest attitude among employees in the sample studied. The lack of safety interest was due to safety ignorance, negligence, lack of safety experience, violation of safety procedures and attitudes. This study showed that the control of safety performance level depends upon controlling the interfaces between the various stages of the refurbishment construction process, i.e. pre-bid, post-bid and construction process. The planning performance measurements this study used were, cost variance, loss time variance, accidents and the extent of planning in the refurbishment projects. This study also identified that the integration mechanisms to be adopted in the safety planning and control process were equally based on the complexity of refurbishment projects, the management safety accountability of the refurbishment organizations and the safety performance targeted.